Corporate Governance and Financial Resilience: Systematic Literature Review and Bibliometric Analysis - Lestari, Tri; Ahmad, Gatot Nizar (Pattimura Proceeding, 2026)
This article examines how firm level research links corporate governance to financial resilience. A corpus of 113 Scopus indexed articles is analysed through performance analysis and science mapping, and is complemented by five systematic or bibliometric reviews that focus on governance, stability and crisis related outcomes. Bibliometric indicators are used to trace publication dynamics, leading journals, countries and collaboration networks, while co-occurrence and thematic mapping reveal clusters around board structures, risk governance, ESG oriented governance and crisis performance. A qualitative reading of highly cited and review articles then distils how financial resilience is conceptualised and operationalised, showing that most studies rely on nearby constructs such as financial stability, distress and post shock performance rather than on a harmonised resilience index. The findings portray a rapidly expanding yet uneven field, anchored in a triangle of sustainability, finance and governance journals and dominated by board and banking stability perspectives, with explicit resilience constructs still emerging. By juxtaposing this evidence with existing reviews, the study identifies underexplored combinations of governance mechanisms and resilience outcomes and proposes a more integrated agenda for future firm level research on corporate governance and financial resilience.